Climate change impacts on geotechnical infrastructure: role of unsaturated soil mechanics for adaptation - Pham, Tuan A. (Frontiers in Built Environment, 2025)
Climate change has intensified rainfall variability, droughts, and temperature extremes, amplifying the risks of instability and deformation in geotechnical infrastructure. Traditional saturated soil frameworks are inadequate to capture these effects, whereas unsaturated soil mechanics (USM) offers a more realistic basis for understanding soil behavior under fluctuating hydro-climatic conditions. This paper reviews the critical role of USM in advancing climate-resilient geotechnical engineering. Key challenges include the complexity of soil–atmosphere exchanges, hydraulic hysteresis, scaling from laboratory to field, and uncertainty in climate projections. Concurrently, opportunities are emerging through advanced monitoring, innovative experimental techniques, computational modeling, climate integration, and reliability-based design. By extending classical bearing capacity models, this study integrates USM to more accurately predict geostructure performance. Analytical insights, supported by case studies, demonstrate the influence of rainfall-induced infiltration on slope stability, shallow foundation capacity, and column-supported embankments. Results reveal that suction enhances soil strength but may diminish rapidly during infiltration, heightening failure risk. The study advocates embedding USM into design codes, modeling frameworks, and early-warning systems to move from reactive to proactive resilience. Bridging theory and practice, it provides a pathway for adapting geotechnical systems to climate variability and ensuring long-term infrastructure durability.